1991
DOI: 10.3109/02652049109021876
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial polymerization encapsulation of a viscous pigment mix: emulsification conditions and particle size distribution

Abstract: A viscous organic phase, containing up to 65 per cent solid pigment, was dispersed into water with an emulsifier by a rotor-stator homogenizer and the droplets formed were encapsulated by interfacial polymerization. Microcapsules with volume median diameters d50 ranging from 10 to 25 microns and geometric standard deviation (GSD), from 1.25 to 1.65, were obtained depending on emulsification conditions. Larger impellers gave smaller d50 and slightly narrowed GSD; d50 decreased and GSD increased as volume fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Detailed descriptions of the fabrication process and the fabrication conditions for PUF microcapsules had been reported in many literatures [22][23][24]. The PUF microcapsules filled with a mixture of DGEBPA and BGE were characterized by Fouriertransform infrared (FTIR) spectroscopy, scanning electronic microscope (SEM), optical microscope (OM), metalloscope (MS), differential scanning calorimeter (DSC) and thermogravimetric analyser (TGA) to investigate their chemical structure, surface morphology, size distribution and thermal stability, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed descriptions of the fabrication process and the fabrication conditions for PUF microcapsules had been reported in many literatures [22][23][24]. The PUF microcapsules filled with a mixture of DGEBPA and BGE were characterized by Fouriertransform infrared (FTIR) spectroscopy, scanning electronic microscope (SEM), optical microscope (OM), metalloscope (MS), differential scanning calorimeter (DSC) and thermogravimetric analyser (TGA) to investigate their chemical structure, surface morphology, size distribution and thermal stability, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In situ encapsulation of water-immiscible liquids by the reaction of urea with formaldehyde at acid pH is outlined by Dietrich et al (1989). Tan et al (1991), Yan et al (1993), Alexandridou and Kiparissides (1994) and Ovez et al (1997) have all shown that microcapsule size can be controlled by adjusting the agitation rate during microencapsulation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the mean particle size decreased with increasing the content of the emulsifier (Kwon and Kim, 2006). Generally, an emulsifier with lower interfacial tension produces smaller microcapsules (Tan et al, 1992). Ni et al (1995) found that the diameter of microcapsules decreased as the emulsifying time was increased at the initial 3 min, beyond which no appreciable changes in the diameter were observed.…”
Section: -Severalmentioning
confidence: 96%